The Complement System at the Embryo Implantation Site: Friend or Foe? - Bulla, R. (Frontiers Research Foundation, 2012)
An inflammatory-like process and vascular remodeling represent the main changes that occur in decidua in the early phase of pregnancy. These changes are partly induced by trophoblast cells that colonize the decidua and are also contributed by the complement system, which can easily be activated as a result of tissue remodeling. Local control by several complement regulators including surface-bound and soluble molecules is critical to prevent complement-mediated tissue damage in normal pregnancy. C7 expressed on the endothelial cells (ECs) surface has been recognized as a novel complement regulator involved in the control of the proinflammatory effect of the terminal complement complex. The protective role of placental complement regulators in pregnancy is underscored by the recent finding of an association of preeclampsia with mutations in the genes encoding for some of these proteins. Complement components produced at feto-maternal interface serve an important function in placental development. C1q synthesized by decidual ECs and expressed on the cell surface is particularly important in this regard because it acts as a molecular bridge between endovascular trophoblast and ECs. C1q is also produced by extravillous trophoblast and is used to favor trophoblast migration through the decidua. Defective expression of C1q by trophoblast is associated with impaired trophoblast invasion of decidua and may have important implications in pregnancy disorders such as preeclampsia characterized by reduced vascular remodeling.